2010
DOI: 10.1242/jeb.045567
|View full text |Cite
|
Sign up to set email alerts
|

The catecholamine release-inhibitory peptide catestatin (chromogranin A344-364) modulates myocardial function in fish

Abstract: ISO-and endothelin-1-induced positive inotropism and coronary constriction . Thus, besides its antihypertensive properties, CST is now emerging as a novel cardiac modulator, which would protect the heart against excessive systemic and/or intra-cardiac excitatory stimuli (e.g. catecholamines and endothelin-1). Accepted 4 August 2010 SUMMARY Catestatin (CST), the 21-amino acid, cationic and hydrophobic peptide proteolytically derived from the ubiquitous chromogranin A (CgA), is an endogenous inhibitor of catecho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…␤ 1 -AR, coupled to G s proteins, is responsible for positive inotropism and lusitropism, while ␤ 2 -AR, mainly coupled to G i/o proteins, is responsible for the opposite effects on contractility and relaxation (82). The heart of mammalian (23,24,69,2) and nonmammalian (33,49) vertebrates also expresses G i/o -protein-coupled ␤ 3 -AR, which induces negative inotropism and lusitropism (2,23). Activated by physio-pathological nor- adrenaline concentrations, ␤ 3 -ARs counteract the effects induced by catecholamine hyperstimulation (22).…”
Section: ␤-Adrenergic and Et-1 Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…␤ 1 -AR, coupled to G s proteins, is responsible for positive inotropism and lusitropism, while ␤ 2 -AR, mainly coupled to G i/o proteins, is responsible for the opposite effects on contractility and relaxation (82). The heart of mammalian (23,24,69,2) and nonmammalian (33,49) vertebrates also expresses G i/o -protein-coupled ␤ 3 -AR, which induces negative inotropism and lusitropism (2,23). Activated by physio-pathological nor- adrenaline concentrations, ␤ 3 -ARs counteract the effects induced by catecholamine hyperstimulation (22).…”
Section: ␤-Adrenergic and Et-1 Involvementmentioning
confidence: 99%
“…We have recently shown that, in addition to its vasodilatory and antihypertensive influence, CST exerts inhibitory modulation on the mechanical performance of both basal and adrenergically stimulated cardiac preparations from eel (33), frog (49), and rat (2). Our ex vivo studies in the Langendorff-perfused rat heart revealed that CST dose dependently decreased left ventricular pressure (LVP), rate pressure product, and both positive and negative LVdP/dt.…”
mentioning
confidence: 92%
“…Initially identified as a physiological brake in catecholamine secretion (7), CST has been established as a pleiotropic hormone having effects on promoting angiogenesis (10), lowering of blood pressure (8,11,12), and cardiac contractility (13)(14)(15), as well as enhancing baroreflex sensitivity (16,17) and heart rate variability (18).…”
mentioning
confidence: 99%
“…[30] Catestatin is the first known endogenous compound able to inhibit in vitro catecholamine release from both chromaffin cells and noradrenergic neurons by acting as a non-competitive nicotinic cholinergic antagonist. [31] Angelone et al, (2008) [32] hypothesized that circulating levels of catestatin decreased in the plasma of patients with essential hypertension. Genetic ablation of the chromogranin A (Chga) gene in mice increases blood pressure and pretreatment of Chga-null mice with Cts prevents blood pressure elevation indicating a direct role of Cts in preventing hypertension.…”
Section: Discussionmentioning
confidence: 99%